2020
DOI: 10.1051/climat/202017009
|View full text |Cite
|
Sign up to set email alerts
|

Intensité et spatialisation de l’îlot de chaleur urbain parisien à partir de données participatives

Abstract: L’îlot de chaleur urbain est une des principales manifestations du climat urbain qui se caractérise par des températures plus élevées en ville qu’à la campagne et peut avoir des conséquences importantes pour les citadins en particulier lors des vagues de chaleur. Par convention, l’intensité de l’îlot est calculée, à partir des données des stations météorologiques de référence, comme la différence de température de l’air entre les zones urbaines et rurales environnantes. Dans cet article, nous cherchons à quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…However, studies have shown that the instrument has an inbuilt lag and that if it is not positioned in shade then it is vulnerable to radiative overheating from direct sunlight (Büchau, 2018; Coney et al, 2022; Meier et al, 2017). Moreover, if the owner does not specify their location, a false location may be assigned using the IP address of the assigned wireless network (Madelin & Dupuis, 2020; Meier et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, studies have shown that the instrument has an inbuilt lag and that if it is not positioned in shade then it is vulnerable to radiative overheating from direct sunlight (Büchau, 2018; Coney et al, 2022; Meier et al, 2017). Moreover, if the owner does not specify their location, a false location may be assigned using the IP address of the assigned wireless network (Madelin & Dupuis, 2020; Meier et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…There have been a considerable number of studies that have explored such sources for temperatures in individual cities-Berlin (Meier et al, 2015), London (Chapman et al, 2017), Amsterdam (De Vos et al, 2017), Paris (Madelin & Dupuis, 2020), Oslo (Venter et al, 2020), Moscow (Varentsov et al, 2020), Sydney (Potgieter et al, 2021)-and increasingly for other parameters (De Vos et al, 2020). These have consistently found parts of cities to be considerably hotter than the NMS networks suggest, particularly during heatwaves.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meier et al (2017) suggested to elaborate a quality control, since then enriched by Varentsov et al (2020) on Moscow and Feichtinger et al (2020) on Vienna. Madelin and Dupuis (2019) developed another statistical method evaluated on Paris and Napoly et al (2018) proposed a quality control process that can operate without any temperature reference in Berlin, Toulouse, or Paris. In previously cited case studies, the percentage of deleted observations ranged from 40% to 75% depending on the method.…”
mentioning
confidence: 99%